Sistem Pendukung Keputusan Penentuan Penerima Beasiswa Menggunakan Metode Grey Relational Analysis - Handoko, Dwi (Journal of Information Technology, Software Engineering and Computer Science (ITSECS), 2024)
The determination of scholarship recipients in schools is a process that considers a variety of factors to ensure that educational assistance is allocated to students in need and have the potential for academic success. The problem in determining scholarship recipients is the difficulty in assessing criteria that cannot be easily measured, such as academic potential or social contribution, which can influence selection decisions. This study aims to determine scholarship recipients by applying the Gray Relational Analysis (GRA) method so that GRA's ability to handle uncertainty and vagueness in data will be a decision recommendation for determining scholarship recipients. The results of the alternative ranking of rank 1st were obtained by Students HE, 2nd place was obtained by Students AB, 3rd place was obtained by Students LS, 4th place was obtained by Students BY, 5th place was obtained by Students GM, 6th place was obtained by Students DT, and 7th place was obtained by Students YD.